The impact of regional and catchment characteristics on long-term runoff in small agricultural catchments in Latvia. Issue 2 (25th January 2022) - Veinbergs, A.; Lagzdins, A.
Abstract: The explanation of runoff behavior is challenging due to variable weather conditions, and catchment characteristics. The parameter equifinality in catchment-scale models turns into the uncertain distribution of water balance components even though models tend to represent total runoff well. This study aims to discuss long-term runoff and evapotranspiration (ET) variations affected by regional allocation and catchment characteristics in Latvia. The study applies the observational runoff data from drainage fields and small catchment scales. The sites represent the spatially different regions in Latvia with relatively variable yearly precipitation amounts. The robust data of surface slope gradients, the share of subsurface drainage systems, arable and grasslands, and ditch networks describes the differences in the catchment characteristics. The results reveal that higher long-term yearly average runoff and ET rates are experienced by the regions with higher yearly precipitation amounts. Simultaneously, the higher the long-term yearly average precipitation and steeper the surface slope gradient, the proportionally (%) higher is the runoff contribution into the water balance. When compared with the small catchments, the soil profiles at drainage fields might store more water after the subsurface drainage runoff is running short. Consequently, the small catchments might experience the later response of subsurface drainage runoff after the dry seasons. HIGHLIGHTS: This study quantifies the impacts of regional allocation and site-specific catchment characteristics on the variations in long-term and yearly runoff and ET rates The results will be further practically applied for regionalization of model parameters and validation of simulated runoff and ET rates. Results will enable planning of appropriate nutrient mitigation measures in poorly or ungauged catchments.